LITURGY AS HISTORY: THE ORIGINS OF THE EXETER MARTYROLOGY - Hamilton, Sarah (Traditio, 2019)
Through an Anglo-Norman case study, this article highlights the value of normative liturgical material for scholars interested in the role that saints’ cults played in the history and identity of religious communities. The records of Anglo-Saxon cults are largely the work of Anglo-Norman monks. Historians exploring why this was the case have therefore concentrated upon hagiographical texts about individual Anglo-Saxon saints composed in and for monastic communities in the post-Conquest period. This article shifts the focus away from the monastic to those secular clerical communities that did not commission specific accounts, and away from individual cults, to uncover the potential of historical martyrologies for showing how such secular communities remembered and understood their own past through the cult of saints. Exeter Cathedral Library, MS 3518, is a copy of the martyrology by the ninth-century Frankish monk, Usuard of Saint-Germain-des-Prés, written in and for Exeter cathedral's canons in the mid-twelfth century. Through investigation of the context in which it was produced and how its contents were adapted to this locality, this article uncovers the various different layers of the past behind its compilation. It further suggests that this manuscript is based on a pre-Conquest model, pointing to the textual debt Anglo-Norman churchmen owed to their Anglo-Saxon predecessors.